Exercise, Nutrition, and Supplements in the Muscle Carnitine Palmitoyl-Transferase II Deficiency: New Theoretical Bases for Potential Applications - Negro, Massimo; Cerullo, Giuseppe; Parimbelli, Mauro; Ravazzani, Alberto; Feletti, Fausto; Berardinelli, Angela; Cena, Hellas; D’Antona, Giuseppe (Frontiers in Physiology, 2021)
Carnitine palmitoyltransferase II (CPTII) deficiency is the most frequent inherited disorder regarding muscle fatty acid metabolism, resulting in a reduced mitochondrial long-chain fatty acid oxidation during endurance exercise. This condition leads to a clinical syndrome characterized by muscle fatigue and/or muscle pain with a variable annual frequency of severe rhabdomyolytic episodes. While since the CPTII deficiency discovery remarkable scientific advancements have been reached in genetic analysis, pathophysiology and diagnoses, the same cannot be said for the methods of treatments. The current recommendations remain those of following a carbohydrates-rich diet with a limited fats intake and reducing - and even excluding - physical activity, without, however, taking into account the long-term consequences of this approach. Suggestions to use carnitine and medium chain triglycerides remain controversial; conversely, other potential dietary supplements able to sustain muscle metabolism and recovery from exercise have never been taken into consideration. The aim of this review is to clarify biochemical mechanisms related to nutrition and physiological aspects of muscle metabolism related to exercise in order to propose new theoretical bases of treatment which, if properly tested and validated by future trials, could be applied to improve the quality of life of these patients.